Fault slip of the 2022 Mw6.7 Menyuan, China earthquake observed by InSAR, and its tectonic implications - Yang, Yuetong; Song, Xiaogang; Gong, Wenyu; Qu, Chunyan (Frontiers in Earth Science, 2023)
In this article the ascending and descending Sentinel-1A satellite data are used to investigate the coseismic slip model of the 2022 Mw6.7 Menyuan earthquake in Qinghai, China. The optimal slip model indicates that this event ruptured two fault segments. The main rupture concentrated on the western Lenglongling fault (LLLF) with a purely left-lateral striking-slip motion. A small part of the eastern Tuolaishan fault (TLSF) section was also ruptured, and the motion on it is mainly oblique slip at depth, with an obvious thrust component. Combined with the rupture characteristics of historical events, GPS velocity map, and slip rate studies, we suggest that the TLSF–LLLF junction is a demarcation point where the deformation partitioning pattern has changed. Along the whole LLLF segment, the oblique convergence has completely partitioned into slip on the purely strike-slipping LLLF and thrusting faults in the north. The TLSF segment accommodates a fraction of compressional shortening, which compensates for the discrepancy in the left-lateral slip rate between the LLLF and TLSF. Such transformation in the strain partitioning pattern is likely to be determined by the geometric relationship between the fault strike and the direction of regional block movement.